Discovering the Discourse of Internet Political Memes - Brian McClure (Adult Education Research Conference, 2016)
With more adults engaging in political activity on social media sites such as Facebook, one popular form of communicating ideas--memes--has emerged. This form contributes to a particular discourse that has yet to be identified, examined, and clarified, the purpose of this paper.
Keywords: Political meme discourse; social media